The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12894-020-00714-2
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of TRPM7 prevents tumor growth, migration, and invasion through the Src, Akt, and JNK pathway in bladder cancer

Abstract: Background Bladder cancer (BC) is one of the most common malignancies of the urinary tract. The role of transient receptor potential melastatin 7 (TRPM7) in BC remains unclear. The aim of this study was to investigate the function and signal transduction pathway of TRPM7 in BC. Methods T24 and UMUC3 cells were used to evaluate the molecular mechanism of TRPM7 by immunoblot analysis. Small interfering RNA was used to knockdown TRPM7, and the effect of silencing TRPM7 was studied by wound healing, migration, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 46 publications
(56 reference statements)
2
19
0
1
Order By: Relevance
“…In our experiments, we identified JNK as an important MAP kinase involved in cortactin overexpression in response to CagA. JNK is a major kinase regulating migration of various human cell types (C. Huang, Rajfur, Borchers, Schaller, & Jacobson, 2003; Z. Huang, Yan, & Ge, 2008; E. H. Lee et al, 2020; Xu & Hu, 2020). Our studies are in agreement with other studies showing that transgenic CagA can induce JNK activation in Drosophila (Wandler & Guillemin, 2012).…”
Section: Discussionmentioning
confidence: 82%
“…In our experiments, we identified JNK as an important MAP kinase involved in cortactin overexpression in response to CagA. JNK is a major kinase regulating migration of various human cell types (C. Huang, Rajfur, Borchers, Schaller, & Jacobson, 2003; Z. Huang, Yan, & Ge, 2008; E. H. Lee et al, 2020; Xu & Hu, 2020). Our studies are in agreement with other studies showing that transgenic CagA can induce JNK activation in Drosophila (Wandler & Guillemin, 2012).…”
Section: Discussionmentioning
confidence: 82%
“…To illustrate, it has been established that Ca 2+ channels play important roles both in the control of cellular growth and proliferation and in the control of cell death [ 25 ]. In recent years, several studies reporting that TRPM7 plays an important role in carcinogenesis and claim that it can be considered as a potential target in the treatment of various cancers have attracted attention [ 9 , 12 ]. As Ca 2+ is an important regulator of cell cycle and proliferation, TRPM7, which is a special member of the TRP channels known to be permeable to Ca 2+ and Mg 2+ , is thought to be highly important in terms of cancer cell biology [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that TRPM7 is overexpressed in human pulmonary carcinoma and pancreatic adenocarcinoma [ 29 , 30 ]. In addition, the inhibition and downregulation of TRPM7 by specific chemical agents is known to inhibit the migration and invasion of breast cancer cells, while overexpression has been shown to support the proliferation and migration of lung cancer cells [ 12 , 29 ]. According to Luanpitpong et al, blocking of TRPM7 has repressed cell motility in various non-small-cell lung carcinoma cell lines and patient-derived primary tumor cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations